1999
DOI: 10.1002/jlb.66.3.429
|View full text |Cite
|
Sign up to set email alerts
|

Synovial PMN show a coordinated up-regulation of CD66 molecules

Abstract: Changes in the expression of various activation-dependent surface markers have been reported for polymorphonuclear neutrophils (PMN) isolated from synovial fluid of patients with inflammatory joint diseases. We extend these findings to the expression of CD66 molecules and several other surface markers. Three members of the CD66 family, namely CD66a, CD66b, and CD66c, showed an up to fourfold up-regulation on synovial fluid PMN compared with peripheral blood PMN (PBG) of the same patients; CD59 was increased tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
13
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
5
13
0
Order By: Relevance
“…The pattern in the regulation of the analyzed adhesion molecules observed in the present study clearly fits into results on regulation of adhesion molecules after leukocyte activation induced by cytokines [8,13,14].…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The pattern in the regulation of the analyzed adhesion molecules observed in the present study clearly fits into results on regulation of adhesion molecules after leukocyte activation induced by cytokines [8,13,14].…”
Section: Resultssupporting
confidence: 84%
“…As previously reported we also detected high levels of cytokines (IL-6, IL-8, GM-CSF) within conditioned media obtained by the interaction of leukocytes with CaP-coated samples in contrast to respective conditioned media where noncoated samples were used [6]. Furthermore, the upregulation of CD66b on PMN within inflamed synovial fluid has been shown [14] indicating the regulation of adhesion molecules by soluble mediators in vivo.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…To confirm the activated state of SF neutrophils in our preparations, we analyzed the surface expression of three membrane markers of inflammatory activation, L-selectin (CD62L), CD66b and CD11b, on freshly isolated PB and SF neutrophils (Table 1). Neutrophil extravasation and migration into the inflamed tissue leads to L-selectin shedding and concomitant translocation of CD66b and CD11b from intracellular mobilizable compartments onto the plasma membrane [29][30][31]. As expected, L-selectin surface expression was significantly diminished on SF neutrophils (Table 1) consistent with L-selectin shedding upon granulocytes transmigration into the inflamed areas [29].…”
Section: Release Of Supar By In Vivo Activated Sf Neutrophilssupporting
confidence: 78%
“…6 7 Furthermore, in numerous studies evidence for activation of PMN in synovial fluid (SF) has been reported, particularly the modulation of activation associated surface receptors, including for example, CD66a-c, CD35, CD46, or CD11a/b. [8][9][10] Because PMN have a reservoir of receptors and cytokines, and a propensity to generate and release cytotoxic and proteolytic entities, they may contribute to cartilage destruction. Numerous reports on the role of PMN in the development of tissue damage have been published, including, for example, lesions occurring in ischaemia reperfusion and lung injury, 11 12 in the development of chronic wounds, 13 or in chronic inflammatory diseases, including RA.…”
mentioning
confidence: 99%